In situ transesterification of Chlorella sp. using LiOH-pumice as heterogeneous catalyst - Doliente, Lorenzo Miguel T.
The search for sustainable and renewable resources of energy continues to grow as nations around the world realize the inevitable depletion of fossil fuel resources and the environmental challenges associated with their use.Biodiesel is an attractive alternative liquid fuel that can be used as a substitute to conventional fossil fuel-derived petroleum diesel.In this study,LiOH-pumice synthesized by the wet impregnation method was used as heterogeneous base catalyst in the production of biodiesel from Chlorella sp. Biomass.In situ transesterification was carried out with the aim of studying the effect of reaction temperature,reaction time,catalyst amount,and methanol to biomass ratio on the % fatty acid methyl ester(FAME) Yield.N-hexane(12 mL/g n-hexane to biomass ratio)was used in all of the transesterification reactions as algal lipid extraction solvent.The highest % FAME Yield obtained was 47% at the reaction temperature of 80 0C,reaction time of 3h,catalyst amount of 20 wt %(dry microalgae),and methanol to biomass ratio of 12 mL/g.The characteristics of LiOH-pumice were analyzed by X-ray Diffraction, Fourier Transform Infrared Spectroscopy,Scanning Electron Microscopy-Energy-Dispersive X-ray Spectroscopy,and Brunauer--Emmett-Teller Sorptometry.